Positive Animal Welfare: Bridging the Gap or Raising Inequalities Worldwide? - Rault, Jean-Loup; Sandøe, Peter; Sonntag, Quixi; Stuardo, Leopoldo (Frontiers in Animal Science, 2022)
Positive animal welfare (PAW) is a rising topic in animal welfare science, although its construct, definition and operational approach are still debated. Despite this scientific uncertainty, there is societal interest to include more indicators of positive welfare in legislation, animal welfare assessment and accreditation schemes. Changes in some farming practices seem to be in line with promoting PAW (e.g. free-range housing), providing animals more opportunities for positive experiences such as rewarding natural behavior, greater autonomy or choice. Interestingly, some of the ideas underlying PAW are present in extensive production systems or low-input animal management practices that are common in low-income countries, for example free-roaming livestock or village dogs. Nevertheless, welfare challenges such as neglect, diseases, poor nutrition, animal abuse and other forms of suffering remain ubiquitous, especially where resources like veterinary support are limited. Living conditions for animals in low-income countries provide examples of the delicate balance between positive welfare and welfare risks relating to health and survival, with inextricable ethical dilemmas. In our view, the growing focus on PAW could stimulate a more balanced approach to animal welfare worldwide, promoting PAW while simultaneously limiting welfare challenges. However, we argue that this requires accounting for human factors such as societal and cultural location-specific aspects to find solutions that also benefit and respect people whose livelihood may also be at stake. Those human factors also modulate the consideration and importance of providing animals with positive welfare states and the role of underlying ethical concepts like happiness and a ‘good life’.